Digital Correlation of First Order Space Time in a Fluctuating Medium - B. Santoso (Atom Indonesia, 2006)
The study of fluctuating medium has been of great interest through the use of the correlation techniques A laser beam is known to form a coherent beam which  can be made to propagate within the fluctuating medium. This will allow the  study of the outgoing beam using digital correlation technique. Based on  the power spectrum, the integral transformation of the correlation function,  one can obtain for instance the radius and mass of the particles executing Brownian motion in the dispersed solution. To correlate the laser beam directly may not allow the detection of  signals by electronic means. A method of digitizing the light signals  by means of light beat heterodyne technique is  therefore adopted. The temporal and special correlation functions can be measured